Leadership in the Time of COVID-19: Reflections of Latin American Higher Education Leaders - Samoilovich, Daniel (International Higher Education, 2020)
To navigate the storm of the COVID-19 pandemic, university leaders should consider its structural impact on teaching and learning, research and innovation, decision-making structures, and on their own role in providing the academic community with a strong vision. As Shakespeare wrote in As You Like It, “Sweet are the uses of adversity, Which like the toad, ugly and venomous, Wears yet a precious jewel in his head.”